Optimal workpiece positioning in flexible fixtures for thin-walled components. (February 2018) - Do, Minh Duc; Son, Younghoon; Choi, Hae-Jin
Abstract: Flexible fixtures are finding widespread use in manufacturing processes of thin-walled components in the automotive and aerospace industries. Owing to its reconfigurability, a flexible fixture can take different layouts depending on the workpiece geometry and location. By finding the appropriate workpiece location, the deformation of workpieces under machining forces and their own weights can be reduced, hence increasing the quality of the final products. In this paper, we introduce a novel method for optimum workpiece positioning in rod type flexible fixtures for thin-walled components. First, the geometry of the workpiece is extracted from its CAD model. Second, a geometry-based method is proposed to find the optimal location of the workpiece relative to the fixture system. A composition of homogeneous transformations is performed to maximize the workpiece support capacity, initially place the workpiece in the fixture region, and maximize the number of active fixture elements (fixels). Third, the result is verified and visualized in a fixture verification module. An aircraft body panel is employed as an example to test the performance of the proposed method. Finally, conclusions and future studies are discussed. Graphical abstract: Highlights: We proposed a novel workpiece positioning method of flexible fixtures. The workpiece positioning was reduced to 2D polygon problems. The number of supports was maximized by optimizing a point-in-polygon problem. The cutting-tool fixture interference was avoided automatically.